No-Envy Arrow's Conditions - Vincenzo Denicolò (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1996)
This paper studies the relationship between the theory of distributive justice based on the concept of envy-freeness and Arrovian social choise theory. We define two conditions of No-envy and study their relationship with Arrow' scondition of independence of irrelevant alternatives, a weakening of this condition called Personal States Independence and the condition of Minimal Equity, that says that each individual must have the power to veto (in a limited sense) at least one alternative (presumably, one alternative which is particularly unfair to him).
Keywords: 330